Effect of permeability enhancers on paracellular permeability of acyclovir. (7th April 2016) - Ates, Muge; Kaynak, Mustafa Sinan; Sahin, Selma
Abstract: Objectives: According to Biopharmaceutics Classification System (BCS), acyclovir is a class III (high solubility, low permeability) compound, and it is transported through paracellular route by passive diffusion. The aim of this study was to investigate the effect of various pharmaceutical excipients on the intestinal permeability of acyclovir. Methods: The single-pass in-situ intestinal perfusion (SPIP) method was used to estimate the permeability values of acyclovir and metoprolol across different intestinal segments (jejunum, ileum and colon). Permeability coefficient ( P eff ) of acyclovir was determined in the absence and presence of a permeation enhancer such as dimethyl β-cyclodextrin (DM-β-CD), sodium lauryl sulfate (SLS), sodium caprate (Cap-Na) and chitosan chloride. Key findings: All enhancers increased the permeability of paracellularly transported acyclovir. Although Cap-Na has the highest permeability-enhancing effect in all segments, permeation-enhancing effect of chitosan and SLS was only significant in ileum. On the other hand, DM-β-CD slightly decreased the permeability in all intestinal segments. Conclusions: These findings have potential implication concerning the enhancement of absorption of paracellularly transported compounds with limited oral bioavailability. In the case of acyclovir, Cap-Na either alone or in combination with SLS or chitosan has the potential to improve its absorption and bioavailability and has yet to be explored.